Correlation between Cryptosporidium parvum and Helicobacter Pylori Infections in Gastrointestinal Patients at Wasit Province - Abdulsada A. Rahi; Safa A. Fadhil (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present study aimed to identify the relationship between Cryptosporidium parvum parasite andHelicobacter pylori in patients at Wasit province and its environs. One hundred stool samples were collected(male and female) from suspected diarrheal patients of parasitic and bacterial infection during the periodOctober 2020 to April 2021 who attended to Al-Karamah Teaching Hospital at Wasit province and GeneralHospital of Martyr Fairuz at Hay district.The investigation of the oocysts of the Cryptosporidium parvum parasite was carried out by staining withModified Ziehl Neelson method and also detecting of Helicobacter pylori by using dipstick. The results ofour study revealed that 55( 55%) was positive for C. parvum and 48 (48%) was positive for Helicobacterpylori and the co- infections between the parasite and bacteria reached to 32( 32%). The age group(1-20years) showed the highest11 (11%) prevalence rate while the lowest prevalence was in patient with agegroup (21-40 years) reached to 6(6%) interplay infections between the parasite and bacteria .